The effect of calcium ions in the adsorption and photocatalytic oxidation of humic acid - Mariquit, Eden (Animo Repository, 2009)
The effect of calcium ion concentration on the photocatalytic oxidation of humic acid (HA) solution at pH range 7.5-8.5 was investigated. The experiments were conducted using different concentrations of commercially available titanium dioxide (Aeroxide® TiO2 P25, Nippon Aerosil Co. Ltd.). Initially, a study conducted in the dark was done to determine the adsorption of HA onto the titanium dioxide (TiO2). After that, the effect of UV irradiation in humic acid and the photodegradation of HA in the presence of UV irradiation as a function of calcium ion concentration and titanium dioxide were investigated. Results indicated that pH 8.0 ± 0.5, there is insignificant adsorption of HA onto the surface of TiO2. But upon addition of calcium ions, adsorption of HA was facilitated. The experiment established the effect of calcium ions and catalyst concentration on the adsorption of HA onto TiO2. During photolysis, results showed that irradiation of the water sample with UV light (λ=360 nm) affected only the color of the solution. In the photocatalytic experiment, the degradation of HA is reported in terms of its absorbance at 254 nm and 436 nm, corresponding to the aromatic compound content and the color of the solution respectively. The results showed that adding calcium ions increased the rate of photocatalytic oxidation of humic acids at pH 8.0 ± 0.5. Copyright © 2009 The Society of Chemical Engineers, Japan.